2021
DOI: 10.1371/journal.pone.0254812
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome and diabetes mellitus type-2 and their association with intake of dairy and legume in Andean communities of Ecuador

Abstract: Metabolic syndrome (MetS) and type 2 diabetes (T2D) are metabolic alterations associated with high morbidity and mortality, particularly in low and middle-income countries. Diet has a significant impact on the risk to develop MetS and T2D; in this regard, consumption of fruits, vegetables, and protein rich foods (from plant and animals) are important to prevent and manage these pathologies. There are limited studies regarding the potential association between Andean foods rich in proteins and the presence of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
1
4
0
4
Order By: Relevance
“…The study also found that of patients with high blood pressure, only 19% are adequately controlled [7]. In addition, in this same population, a prevalence of 42% of metabolic syndrome, 10% of type-2 diabetes mellitus, and 66.2% hypercholesterolemia have been reported, which demonstrates the high frequency and severity of these problems in this community [8].…”
Section: Introductionmentioning
confidence: 51%
“…The study also found that of patients with high blood pressure, only 19% are adequately controlled [7]. In addition, in this same population, a prevalence of 42% of metabolic syndrome, 10% of type-2 diabetes mellitus, and 66.2% hypercholesterolemia have been reported, which demonstrates the high frequency and severity of these problems in this community [8].…”
Section: Introductionmentioning
confidence: 51%
“…16 Additionally, a case-control study of 1997 individuals showed that legume intake was inversely associated with T2D risk (≥1 servings per day: odd ratio (OR), 0.33; 95% CI, 0.14–0.94). 17 Additionally, one cohort study found that people consuming vegetables ≥4 servings per day had a lower risk of T2D based on 1485 participants, which was both observed in men (HR, 0.56; 95% CI, 0.34–0.92) and women (HR, 0.29; 95% CI, 0.16–0.53). 18 Furthermore, a meta-analysis showed that green leafy and cruciferous vegetables had a borderline inverse association with T2D risk.…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…En Venezuela el notable ascenso tanto de la mortalidad general como de la cardiovascular observado en los últimos años, pese al desarrollo y perfeccionamiento de los medios para su diagnóstico y tratamiento, señala el problema del acceso a éstos por parte de la población necesitada de tales cuidados, enfrentada a dos realidades adversas, una del sistema público de prestaciones sanitarias y a la del sistema privado, fuera del alcance de la gran mayoría, como consecuencia de la pérdida del valor monetario y adquisitivo, lo que explica plausiblemente el incremento sostenido en la mortalidad por ECV en la última década (Duran et al, 2023). Baldeón et al, (2021) describen en Ecuador al evaluar a 1.997 personas de entre 35 y 70 años (edad media 51 años, 72% mujeres), una prevalencia en el año 2018 del síndrome metabólico de 42% en hombres y 44% en mujeres; mientras la prevalencia de diabetes tipo 2 fue del 9% y 10%, respectivamente. El síndrome metabólico y la diabetes tipo 2 fueron más comunes en mujeres mayores de 50 años con educación primaria o menos, bajos ingresos económicos y con obesidad y fue más frecuente en el área rural, mientras que la diabetes tipo 2 fue más frecuente en el área urbana.…”
Section: Carga Global Por Enfermedades Cardiovascularesunclassified